Federal funds for research, development, and other scientific activities, fiscal years 1965, 1966 and 1967 - National Science Foundation, Washington, DC.; National Science Foundation, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1966)
This report covering the years 1965, 1966, and 1967 is the fifteenth in a series reporting federal obligations and expenditures for scientific programs. The data were obtained by means of a questionnaire formulated and distributed by the national science foundation (nsf) to federal agencies in January and February, 1966. Each agency reported only on funds appropriated to it. This document represents the foundation's interpretation of the statistical data and descriptive material submitted. Amounts for 1965 represent transactions for a completed fiscal year. The data for 1966-67 represent estimates. The description of these activities is organized into three parts--(1) federal funds for research, development, and research and development facilities, (2) funds for activities related to collection and dissemination of scientific and technical information, and (3) funds obligated for the collection, analysis, and publication of general purpose scientific data. Appended are (1) technical notes dealing with adjustments in data, term definitions, limitations in data, and other background information, (2) a list of federal contract research centers, and (3) statistical tables for the three areas of inquiry. This document is also available for $1.25 from the superintendent of documents, U.S. Government printing office, Washington, D.C. 20402. (ds)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Education; Federal Aid; Federal Government; Federal Programs; Information Centers; Information Dissemination; Program Costs; Research; Scientific Research; Technological Advancement; ATOMIC ENERGY COMMISSION -- DEPARTMENT OF DEFENSE -- Department of Health Education and Welfare -- NATIONAL AERONAUTICS AND SPACE ADMINISTRATION -- National Institutes of Health